Electrified Transport Systems – Perspective of Transport for the Third Millennium - Jiri Drabek (Communications - Scientific letters of the University of Zilina, 2001)
Energetics and transport in the contemporary world are based mostly on exploitation of fossil fuels (petroleum, coal, natural gas). Enormous consumption of fossil fuels causes emissions of CO2 and Nox and global atmosphere warming. The supply of fossil fuels in the future is mainly limited by petroleum used for combustion machines of road vehicles and aeroplanes. Under these circumstances, the electric-propelled guided transport systems (electrified railways, maglev) are energetically – and ecologically-suitable solutions for quick and safe transport in the future because electrical energy can be produced also from renewable sources (water potential, wind, sun energy) or from nuclear energy without above-mentioned emissions.